Bioaccumulation of lead by Bacillus species isolated from pig waste - Akujobi CO; Odu NN; Okorondu SI (Journal of Research in Biology, 2012)
Heavy metals, such as lead, copper, cadmium, chromium and mercury are important environmental pollutants, particularly in areas with high anthropogenic pressure. Their presence in the atmosphere, soil and water, even in traces, can cause serious problems to all organisms. Living organisms are exposed in nature to lead commonly in their ionized forms, which at different concentrations affect microbial population. Microorganisms are known to interact with heavy metals through a number of mechanisms including intracellular accumulation. Bacillus species isolated from pig waste was exposed to different concentrations of lead solution within 24 hours. The percentage log survival / growth rate in the different concentrations of lead was determined periodically. Bioaccumulation of lead by the test isolate was determined in the graded lead concentrations (0, 1.10, 100. 500 μg/ml). The result showed that the growth of the isolate was progressively inhibited by lead in a dose dependent fashion. The isolate showed a potential to survive lead intoxication and accumulated the toxicant. Therefore, Bacillus species isolated from pig waste shows a promise for its use in bioremediation of lead polluted environments. This can be applied as organic manure together with the microorganism in heavy metal-polluted site to prevent heavy metal toxicity and to enhance the growth of plants